Taxonomic Richness and Diversity of Larval Fish Assemblages in the Oceanic Gulf of Mexico: Links to Oceanographic Conditions - Meinert, Corinne R.; Clausen-Sparks, Kimberly; Cornic, Maëlle; Sutton, Tracey T.; Rooker, Jay R. (Frontiers in Marine Science, 2020)
Biodiversity enhances the productivity and stability of marine ecosystems and provides important ecosystem services. The aim of this study was to characterize larval fish assemblages in pelagic waters of the northern Gulf of Mexico (NGoM) and identify oceanographic conditions associated with areas of increased taxonomic richness (TF) and Shannon diversity (H’). Summer ichthyoplankton surveys were conducted in the NGoM in 2015 and 2016 using neuston net (surface layer; upper 1 m) and oblique bongo net (mixed layer; 0-100 m) tows. Over 17,000 fish larvae were collected over the two-year study, and 99 families of fish larvae were present. Catch composition in the surface layer was relatively similar to the mixed-layer catch, with carangids (jacks), scombrids (mackerels, tunas) and exocoetids (flyingfishes) being numerically dominant; however, deep-pelagic species, including myctophids (lanternfishes), gonostomatids (bristlemouths), and sternoptychids (marine hatchetfishes), were present almost exclusively in the mixed layer samples. Generalized additive models were used to evaluate the effect of oceanographic conditions on ichthyoplankton abundance and biodiversity. Salinity and sea surface height (SSH) were the most influential oceanographic conditions, with higher occurrence, higher TF, and higher H’ all present in areas of lower salinity and lower SSH. This study highlights the ecological importance of cyclonic mesoscale features and areas of upwelling as areas of increased biodiversity for larval fishes, and also indicates that the mixed layer in the NGoM is essential habitat for deep-pelagic fishes during the early life interval.